Making Sense of Community Action and Voluntary Participation—A Multilevel Test of Multilevel Hypotheses: Do Communities Act?1. (8th December 2015) - Cope, Michael R.; Currit, Alex; Flaherty, Jeremy; Brown, Ralph B.
Abstract: To what extent does community context influence individuals' proclivity to participate in community‐oriented activities and projects? In this article we utilize survey data from residents of 99 Iowa communities to conduct a multilevel analysis of voluntary participation and community action, simultaneously addressing voluntary participation at the individual level and "community action" at the community level. Additionally, we test the suggestion that community attachment may constitute a unique form of social capital. The robustness of these data allows us to overcome the obstacles that have led to the conflation of individual‐ and community‐level attributes in many community studies. We show that community attachment and community‐oriented action are determined almost entirely by individuals' characteristics rather than by the characteristics of communities, and thus do not constitute community‐level phenomena, calling into question the assumptions on which certain theoretical approaches to community are based.